Pengaruh Gaya Hidup dan Lokasi terhadap Keputusan Pembelian Di Okui Kopi 3.0 Surabaya - Rr Nivita Attyla Putri (Syntax Idea, 2021)
The purpose of the research for indicate the impact of the lifestyles and location on the buying decision in OKUI Kopi 3.0 Surabaya. This type of quantitative research by distributing questionnaires using purposive sampling technique to 63 respondents. The data analysis used the Structural Equation Modelling (SEM) method based on the component which uses the Partial Least Square (PLS) technique. The result of this research reveal that the lifestyles and location variables take a positive effect on buying decision of OKUI Kopi 3.0 Surabaya. With a high lifestyle of the customer and a location or place to comply this lifestyle that is easily accessible to consumers, it will increase consumer decisions to make purchases.